THE DETERMINANTS OF INDIVIDUAL PERFORMANCE IN TALENT MANAGEMENT AND EMPLOYEE MANAGEMENT THROUGH JOB SATISFACTION - Hilmy, Muhammad Fauzi Haidar (jfpublisher, 2023)
Talent management and employee management is one of the crucial factor in the company since they are determine the success and company balance in the future. In addition, the employee who have high motivation in doing his wirk is increasing his job satisfaction in the company itself. The objective of this research is to determine the influence of talent management and employee engagement on job satisfaction and individual performance, both partially and simultaneously. The population consists of employees working in mineral and coal industry at PT ABC, and the survey was conducted the LinkedIn platform. The data collection was using non-probability sampling methods, specifically convenience sampling through the questionnaire. The data analysis was using multiple linear regression analysis and path analysis. The results of this research indicate that talent management and employee engagement, both partially and simultaneously, have a significant influence on job satisfaction. Furthermore, talent management and employee engagement, both partially and simultaneously, affect individual performance among employees in the mineral and coal industry.